Hyperspectral Raman imaging using Bragg tunable filters of graphene and other low‐dimensional materials. (23rd November 2017) - Gaufrès, Etienne; Marcet, Stéphane; Aymong, Vincent; Tang, Nathalie Y‐Wa; Favron, Alexandre; Thouin, Felix; Allard, Charlotte; Rioux, David; Cottenye, Nicolas; Verhaegen, Marc; Martel, Richard
Abstract : Hyperspectral Raman imaging is presented as a powerful method to acquire quantitative as well as qualitative information on low‐dimensional materials. The method is, however, not widely used due to limitations of the Raman scanning instruments. Here we present a hyperspectral Raman system based on Bragg tunable filtering that is capable of global imaging with significantly reduced acquisition time and improved sensitivity compared to scanning confocal Raman microscopes. The operation principles of the instrument are presented, and the performance is benchmarked using a calibrated carbon nanotube sample. Examples of various applications are shown to illustrate the abilities of the technique to characterize samples deposited on oxidized silicon substrates, including graphene stacks prepared by chemical‐vapor deposition, exfoliated MoS2, and carbon nanotubes filled with dye molecules. The wealth of information available through this hyperspectral Raman imaging technique opens many new ways to probe the properties of complex low‐dimensional materials. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Schematic of the optical path between the main components (e.g. Bragg tunable filter) of the system to acquire globally a hyperspectral Raman image of low‐dimensional materials, such as MoS2 .